Convolution Algebraic Structures Defined by Hardy-Type Operators - Pedro J. Miana; Juan J. Royo; Luis Sánchez-Lajusticia (Journal of Function Spaces and Applications)
The main aim of this paper is to show that certain Banach spaces, defined via integral kernel operators, are Banach modules (with respect to some known Banach algebras and convolution products on ℝ+). To do this, we consider some suitable kernels such that the Hardy-type operator is bounded in weighted Lebesgue spaces Lωpℝ+ for p≥1. We also show new inequalities in these weighted Lebesgue spaces. These results are applied to several concrete function spaces, for example, weighted Sobolev spaces and fractional Sobolev spaces defined by Weyl fractional derivation.